Catalytic oxidation of cellobiose over TiO2 supported gold-based bimetallic nanoparticles - Amaniampong, Prince Nana (2016)
A series of Au–M (M = Cu, Co, Ru and Pd) bimetallic catalysts were supported on TiO2via a deposition–precipitation (DP) method, using urea as a precipitating agent. The resulting catalysts were employed in the catalytic oxidation of cellobiose to gluconic acid and the properties of these catalysts were carefully examined using various characterization techniques. Cu–Au/TiO2 and Ru–Au/TiO2 catalysts demonstrated excellent catalytic activities in the oxidation of cellobiose to gluconic acid, though with contrasting reaction mechanisms. Complete conversion of cellobiose (100%) with a gluconic acid selectivity of 88.5% at 145 °C within 3 h was observed for reactions performed over Cu–Au/TiO2; whereas, a conversion of 98.3% with a gluconic acid selectivity of 86. 9% at 145 °C within 9 h was observed for reactions performed over Ru–Au/TiO2. A reaction pathway was proposed based on the distribution of reaction products and kinetic data. It is suggested that cellobiose is converted to cellobionic acid (4-O-beta-D-glucopyranosyl-D-gluconic acid) and then gluconic acid is formed through the cleavage of the β-1,4 glycosidic bond in cellobionic acid over Cu–Au/TiO2 catalysts. On the other hand, for reactions over the Ru–Au/TiO2 catalyst, glucose was observed as the reaction intermediate and gluconic acid was formed as a result of glucose oxidation. For reactions over Co–Au/TiO2 and Pd–Au/TiO2 catalysts, fructose was observed as the reaction intermediate, along with small amounts of glucose. Co and Pd remarkably promoted the successive retro-aldol condensation reactions of fructose to glycolic acid, instead of the selective oxidation to gluconic acid.